THE IMPLEMENTATION OF SCHOOL CULTURE-BASED CHARACTER EDUCATION IN SALEM STATE ELEMENTARY SCHOOL, PONDOKSALAM SUBDISTRICT, INDONESIA - Imam Tabroni; Fitriani Nasihah; Ijah Bahijah (Erudio Journal of Educational Innovation, 2021)
The moral crisis that often occurs in school-age children is the reason for the importance of strengthening character education in every school. This paper describes the concept of character education and the implementation of school culture-based character education. The implementation of school culture-based character education means an effort to establish character values based on programs run by the education unit. The purpose of this study was to determine the implementation of school culture-based character education at SD Negeri Salem, Pondoksalam District. The research method uses descriptive qualitative data collection techniques through interviews, observations, and documentation studies. The informants who were asked for data were the Principal and Deputy Head of the Salem State Elementary School Curriculum. The results show that the implementation of school culture-based character education at SD Negeri Salem has been run through co-curricular activities (in the learning process), habituation of 7 special Poe Atikan, tatanen activities at Bale Atikan, and other habits such as marching activities before entering class, requiring students to bring lunch from home and making it mandatory to clean the classroom before going home from school. Meanwhile, extracurricular activities are still not going well due to various obstacles, namely the lack of adequate facilities, the absence of extracurricular trainers, and because schools are still in the adaptation stage as a result of COVID-19. Evaluation of the character education program is carried out in the form of observation, self-evaluation, student evaluation, student journal notes and conducting deliberation with all school members.